Unknown “Cherubic song” by Maxym Berezovsky from the collection of TSDAMLM: text and contexts - Gomeniuk, Svitlana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Relevance of the study. Among the works of Maksym Berezovsky, contained in the set of manuscripts from the collection of the Central State Archive-Museum of Literature and Art of Ukraine (TsDAMLM, found 441, description 1, cases 2 — 7), there is a four-part composition — "Cherubic Song" in C major, that wasn’t published and researched previously. Based on the voice part-books, the score of this work was drawn up, and its textological and musicological analysis was carried out. The publication of the full text of the score of "Cherubic Song", among with the editorial comments and observations on the style of the piece significantly complements our knowledge about Maksym Berezovsky's creativity. Besides it makes possible to include the piece in performing practice. The main objective of the article is to summarise the experience of working with the handwritten voice books of 18 century and to reveal the stylistic features of M. Berezovsky's "Cherubic Song", especially, the composition, work with words, interaction between harmony and polyphony. Each of the two research stages used its own methods. At the stage of working with manuscripts and compiling the score, comparative, empirical, analytical, and synthetic methods were used. Inaccuracies and errors in the musical text were corrected when compiling the score based on a comparison of the first and second parts (soprano, tenor), and in the case of their absence (bass, alto) — taking into account harmonic, polyphonic and other factors. At the stage of working with the completed score, the method of holistic analysis of the musical work was used. Results and conclusions of the study. "Cherubic Song" by M. Berezovsky is a two-part cycle similar to a prelude and a fugue. The compositional division is due to the structure of the verbal text and the peculiarities of the liturgical order: the first part is sung before the Great Entrance, the second — after. The contrast of parts in M. Berezovsky's composition is ensured by a system of musical means (texture, voice melody, meter). The first part of the piece is an old sonata form, characterised by tonal (tonic — dominant), thematic, structural and textural contrast of parts within the exposition, tonal coordination of themes between exposition and reprise. The second movement is a double fugue with a coherent exposition of themes. The fugue demonstrates such a coordination between harmony and polyphony, where the basic quality of polyphony — fluidity, continuity — is neglected: the composition is built from separate harmonically completed structural blocks, as is characteristic of fugues reaching classicism, in particular, fugues from the other works of M. Berezovsky. The polyphonic and harmonic balance, reliance on the compositional algorithms of fugue and sonata, expressive transmission of the verbal text are factors that give reason to consider "Cherubic Song" as an example of the late style of Maksym Berezovsky.